Evaluation of Intravascular Microdialysis for Continuous Blood Glucose Monitoring in Hypoglycemia: An Animal Model. (July 2014) - Schierenbeck, Fanny; Wallin, Mats; Franco-Cereceda, Anders; Liska, Jan
We have previously shown that intravascular microdialysis in a central vein is an accurate method for continuous glucose monitoring in patients undergoing cardiac surgery. However, no hypoglycemia occurred in our earlier studies, prompting further evaluation of the accuracy of intravascular microdialysis in the hypoglycemic range. Thus, this animal study was performed. A porcine model was developed; hypoglycemia was induced using insulin injections. The pigs were monitored with intravascular microdialysis integrated in a triple-lumen central venous catheter. As reference, venous blood gas samples were taken every 5 minutes and analyzed in a blood gas analyzer. Ethical permission for the animal experiments was obtained from the Stockholm Regional Ethical Committee, reference no N397/09. A total of 213 paired samples were obtained for analysis, and 126 (59.2%) of these were in the hypoglycemic range (<74 mg/dl). Using Clarke error grid analysis, 100% of the paired samples were in region AB and 99% in region A. The ISO standard (ISO15197) was met. Bland–Altman analysis showed bias (mean difference) ± limits of agreement was −0.18 ± 16.2 mg/dl. No influence from glucose infusions was seen. The microdialysis monitoring system was found to be very responsive in rapid changes in blood glucose concentration. This study shows that intravascular microdialysis in a central vein is an accurate method for continuous glucose monitoring in hypoglycemia in a porcine experimental model. Furthermore, the system was not influenced by glucose administration and was found to be responsive in rapid blood glucose fluctuations.